L'atribució hipotètica de Curial e Güelfa a Enyego d'Àvalos (Consideracions sobre un «informe» de L. Badia i J. Torró). - SOLER, ABEL (Scripta, 2017)
The journal Estudis Romànics, 39 (2017) has just published my article "Enyego de Avalos, author of the Curial e Guelfa?", which summarizes a part of my thesis, La cort napolitana d'Alfons el Magnànim: el context del «Curial e Güelfa» (University of València, 2016). It supports the hypothesis that Enyego d'Àvalos -a native of Toledo, educated in Valencia, Philip Maria Visconti's counselor and great Chamberlain of Alfons the Magnanimous, at the Kingdom of Naples- would have been the author of the chivalric anonymous romance Curial e Guelfa. Although unpublished thesis, Lola Badia and Jaume Torró have spoken out against my hypothesis through defamatory statements to the media and a very biased report. My purpose in this article is to refute the supposedly scientific arguments of Lola Badia and Jaume Torró, highlight their prejudices and misunderstandings and claim my right to make my own research and to freely express my interpretations. My thesis, which is the result of years of work in archives and analysis of a selected bibliography, has been prepared in accordance with rigorous scientific methodology. The unusual reaction of Badia and Torró is due to the fact that my hypothesis invalidates many of their approaches, which have caused great confusion among historins of medieval literature, because they place Curial in the Iberian courts of the Trastamara royal family and not in the courts of the duke of Milan and of the King of Naples, in touch with Italian humanism.